PSAK IFRS Convergence in Indonesia: Study Literature - Dwi Urip Wardoyo; Christina Pungky Susanta; Adinda Hasna Jatmiko; Selvi Novitasari; Alvina Dimitri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to identify changes from the adoption of IFRS convergence PSAK in Indonesia, to see what impacts have occurred on the financial statements of companies in Indonesia after the adoption of IFRS. Indonesia adopted IFRS into PSAK since 2012 with the aim of increasing the quality of financial accounting standards in Indonesia, so that the financial reports prepared can be used internationally. The literature review method used is the Systematic Literature Review (SLR). The characteristics of IFRS which focus on fair value to emphasize the accuracy of accounting information in financial statements affect total fixed assets, earnings management and also the value relevance of accounting information. This study identified a reduction in total fixed assets, reduced earnings management and an increase in the value relevance of accounting information using the pricing model in financial statements.